2022
DOI: 10.30773/pi.2021.0361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Attitude Toward Suicide on Suicidal Behavior: Based on the Korea National Suicide Survey

Abstract: attitude toward suicide. This study aimed to extract factors from the Attitude Toward Suicide Scale (ATTS) and investigate the relationship between attitudes toward suicide and suicidal behavior (i.e., suicidal idea, plan, and attempt) by using a representative sample of Korean adults.Methods Three thousand Koreans aged 19 to 75 years were surveyed cross-sectionally in 2013 and 2018. The data collected were subjected to exploratory factor analysis. Extracted attitude factors were compared using a suicidal beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As mentioned earlier, previous studies have established a positive association between pro-suicidal attitudes and suicidal behavior at the individual level [18][19][20][21][22][23][24][25][26][27], including a study of the 2013 and 2018 KNSS data [41]. However, this study reports a negative association between suicide rates and permissive attitudes, where permissive regions had lower suicide rates despite permissive individuals being more likely to engage in suicidal behavior.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…As mentioned earlier, previous studies have established a positive association between pro-suicidal attitudes and suicidal behavior at the individual level [18][19][20][21][22][23][24][25][26][27], including a study of the 2013 and 2018 KNSS data [41]. However, this study reports a negative association between suicide rates and permissive attitudes, where permissive regions had lower suicide rates despite permissive individuals being more likely to engage in suicidal behavior.…”
Section: Discussionmentioning
confidence: 53%
“…Each item of the ATTS was scored on a Likert scale of 1-5 points, where 1 indicated "disagreement" and 5 indicated "agreement." 2.2.1 Factor structure of ATTS Kim et al previously reported a factor structure of ATTS based on the 2013 and 2018 KNSS [41]. In this study, we reevaluated the previous factor structure, as multiple methods for determining the number of factors indicated that a three-factor structure best ts the 2018 KNSS data alone (Supplementary Fig.…”
Section: Measurementsmentioning
confidence: 94%
“…This review found that interventions could be successful in changing beliefs and attitudes. There is evidence of the relationship between attitudes towards suicide and suicidal behaviour; having permissive attitudes towards suicide may increase the odds of suicidal ideation, planning and attempts, while viewing suicide as an unjustified behaviour decreases the odds [ 73 ]. As demonstrated in this review, attitudes towards suicide can be modified.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide, defined as an intentional attempt to hurt oneself, is a complex and multifaceted phenomenon which is influenced by individual, familial, social, and cultural factors (1,2). Suicide consists of a continuum of suicide ideation, planning, and suicide attempts (3). Suicidal ideation and self-harm are considered by the World Health Organization (WHO) as highly important concerns regarding psychological and social health (4,5).…”
Section: Introductionmentioning
confidence: 99%